Mitochondrial Biogenesis Is Impaired in Osteoarthritis Chondrocytes but Reversible via Peroxisome Proliferator–Activated Receptor γ Coactivator 1α. Issue 8 (28th July 2015) - Wang, Yun; Zhao, Xianling; Lotz, Martin; Terkeltaub, Robert; Liu‐Bryan, Ru
<x xml:space="preserve">Abstract</x> Objective The etiology of chondrocyte mitochondrial dysfunction in osteoarthritis (OA) is not completely understood. OA chondrocytes are deficient in the metabolic biosensors active AMP‐activated protein kinase (AMPK) and sirtuin 1 (SIRT‐1), which modulate the mitochondrial biogenesis "master regulator" peroxisome proliferator–activated receptor γ coactivator 1α (PGC‐1α). Moreover, PGC‐1α critically mediates AMPK anticatabolic activity in chondrocytes. The aim of this study was to test the hypothesis that mitochondrial biogenesis is deficient in human OA chondrocytes and that this deficiency functionally increases chondrocyte procatabolic responses, which are reversed by activation of the AMPK/SIRT‐1/PGC‐1α pathway. Methods We assessed the expression and activity (phosphorylation) of AMPKα, SIRT‐1, and PGC‐1α in human knee chondrocytes and human and mouse knee cartilage, and we defined and compared the content and function of mitochondria, including oxidative phosphorylation and expression of mitochondrial biogenesis factors (mitochondrial transcriptional factor A [TFAM] and nuclear respiratory factors [NRFs]). Results Human knee OA chondrocytes had a decreased mitochondrial biogenesis capacity, which was linked to reduced AMPKα activity and decreased expression of SIRT‐1, PGC‐1α, TFAM, NRF‐1, and NRF‐2. Human knee OA and aging mouse knee cartilage had decreased expression of TFAM and ubiquinol–cytochrome c reductase core protein, a subunit of mitochondrial complex III, in situ. Chondrocyte TFAM knockdown inhibited mitochondrial biogenesis and enhanced procatabolic responses to interleukin‐1β. Finally, activation of AMPK by A‐769662 increased PGC‐1α expression via SIRT‐1 and reversed impairments in mitochondrial biogenesis, oxidative phosphorylation, and intracellular ATP in human knee OA chondrocytes. Conclusion Mitochondrial biogenesis is deficient in human OA chondrocytes, and this deficiency promotes chondrocyte procatabolic responses. TFAM‐mediated activation of the AMPK/SIRT‐1/PGC‐1α pathway reverses these effects, suggesting translational potential of pharmacologic AMPK activators to limit OA progression.